2013
DOI: 10.1246/bcsj.20120268
|View full text |Cite
|
Sign up to set email alerts
|

Nanooptical Studies on Physical and Chemical Characteristics of Noble Metal Nanostructures

Abstract: Studies on physical and chemical properties of noble metal nanostructures, mainly by near-field optical microscopy and spectroscopy, are described. Near-field optical microscopy provides optical observation methodology with a spatial resolution in nanometer regime beyond the diffraction limit of light. We developed near-field imaging systems equipped with various light sources including ultrashort pulsed lasers, which enables advanced nonlinear and ultrafast near-field measurements as well as conventional near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 142 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…The extreme malleability of plasmonic responses makes the spectroscopic imaging of their natural nanometer (nano) spatial and femtosecond (femto) temporal scales particularly useful. Scanning techniques, such as near-field microscopy and point-focus photoemission, provide accessible and versatile tools for studies of spatially and temporally resolved plasmonic dynamics, because they are available in many laboratories, versatile, inexpensive, and can be adopted to various environments. The relatively low data acquisition bandwidth of such experiments, however, inhibits experimental investigations of the joint spatiotemporal dynamics of plasmonic excitations. More specialized methods, such as electron microscopy, have extremely high spatial resolution and exceptional spectroscopic capabilities for nanometer scale probing of plasmonic modes, , but again, incorporating time resolution that is sufficient for imaging dynamics of plasmonic phenomena is only starting to be achieved in highly specialized experiments. , It is particularly useful, therefore, to record spatiotemporal movies of plasmon dynamics by microscopic methods with the appropriate spatial and temporal resolution to be able to follow the plasmonic field phase evolution at the local speed of light with the requisite temporal and spatial resolution.…”
Section: Imaging Plasmons With Peemmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme malleability of plasmonic responses makes the spectroscopic imaging of their natural nanometer (nano) spatial and femtosecond (femto) temporal scales particularly useful. Scanning techniques, such as near-field microscopy and point-focus photoemission, provide accessible and versatile tools for studies of spatially and temporally resolved plasmonic dynamics, because they are available in many laboratories, versatile, inexpensive, and can be adopted to various environments. The relatively low data acquisition bandwidth of such experiments, however, inhibits experimental investigations of the joint spatiotemporal dynamics of plasmonic excitations. More specialized methods, such as electron microscopy, have extremely high spatial resolution and exceptional spectroscopic capabilities for nanometer scale probing of plasmonic modes, , but again, incorporating time resolution that is sufficient for imaging dynamics of plasmonic phenomena is only starting to be achieved in highly specialized experiments. , It is particularly useful, therefore, to record spatiotemporal movies of plasmon dynamics by microscopic methods with the appropriate spatial and temporal resolution to be able to follow the plasmonic field phase evolution at the local speed of light with the requisite temporal and spatial resolution.…”
Section: Imaging Plasmons With Peemmentioning
confidence: 99%
“…The SPP coupling depends on the orientation of the crystal edge with respect to the light propagation, but otherwise the SPP imaging involves the same physics as for SPP fields propagating on metal films. One should note that PEEM imaging of a transient process of SPPs propagating along a wire is fundamentally different from other techniques such as SNOM (Scanning near field optical microscopy), which is often used to record the steady state fields such as Fabry–Perot-like plasmon interferences that form when counter-propagating SPP waves from each side of the structure produce standing wave patterns. , In PEEM experiments, such Fabry–Perot modes are not usually evident in imaging because they require time to establish through propagation, reflection, and interference, but that happens after a substantial decay of their amplitudes. In an ultrafast nonlinear imaging experiment such modes do not have time to build up to sufficient strength for nonlinear imaging .…”
Section: Surface Plasmon Polaritonsmentioning
confidence: 99%
“…One of the advantages of the method is facility of polarization-dependent measurements because the aperture probe yields in-plane polarized signals, as mentioned previously. We conducted research on the metal nanostructures based mainly on two methods of aperture-type near-field optical microscopy. One method is the transmission-type measurement performed through the aperture probe to obtain the near-field extinction images of the samples. The other method is the near-field two-photon excitation probability imaging, in which femtosecond optical pulses are irradiated onto the sample through the aperture probe to detect the two-photon-induced photoluminescence from the gold or silver nanostructures as the signal.…”
mentioning
confidence: 99%
“…Scale bars: 100 nm. (Reproduced with permission from refs and . Copyright 2008 and 2013, The Chemical Society of Japan.…”
mentioning
confidence: 99%
“…142 The Imura group demonstrated that 2D plasmon images of a gold hexagonal plate varied significantly with the distance between the probe and surface (Figure 12f). Specifically, the out-of-plane mode was seen to confine electromagnetic fields more tightly 61,141,204 although Mie resonances was rigorously described in studies of near-field imaging of a submicron-structured gold metasurface using SNOM. 208−210 SNOM measurements correspond to an experimental method in which near-field rather than far-field light is detected, whereas Mie resonance is basically based on the concept of far-field light.…”
Section: D Imagingmentioning
confidence: 99%